2021
DOI: 10.1038/s41598-021-87021-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of human brain microvascular endothelial cells exposed to laminin binding protein (adhesion lipoprotein) and Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae invades the CNS and triggers a strong cellular response. To date, signaling events that occur in the human brain microvascular endothelial cells (hBMECs), in response to pneumococci or its surface adhesins are not mapped comprehensively. We evaluated the response of hBMECs to the adhesion lipoprotein (a laminin binding protein—Lbp) or live pneumococci. Lbp is a surface adhesin recently identified as a potential ligand, which binds to the hBMECs. Transcriptomic analysis was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Quantitative real-time PCR was performed on the QuantStudio 7 Flex system (Applied Biosystems) using Power SYBR green (Applied Biosystems). Previously published primer sequences for the CCL2 , CXCL8 ( 76 ), IL6 , and GAPDH (glyceraldehyde-3-phosphate dehydrogenase) ( 77 ) genes were used. Each sample was normalized to GAPDH threshold cycle values ( C T ), and expression was calculated by the ΔΔ C T method.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time PCR was performed on the QuantStudio 7 Flex system (Applied Biosystems) using Power SYBR green (Applied Biosystems). Previously published primer sequences for the CCL2 , CXCL8 ( 76 ), IL6 , and GAPDH (glyceraldehyde-3-phosphate dehydrogenase) ( 77 ) genes were used. Each sample was normalized to GAPDH threshold cycle values ( C T ), and expression was calculated by the ΔΔ C T method.…”
Section: Methodsmentioning
confidence: 99%
“…An initial signaling is mounted immediately after binding of viral ligand to receptor by setting off an innate immune response to protect the cell. Although the HBMECs are not primary immune cells, several signaling events related to the innate immune response are evoked in response to the attachment of pathogen or its ligands on cell surface 78 – 80 . In the present study we found deregulation of several genes involved in immediate cell response mediated through pattern recognition receptors (PRRs) and downstream interferon signaling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Libraries for RNA sequencing were prepared exactly as described in our previous publication 80 using QuantSeq 3′ mRNA-Seq Library Prep Kit (Lexogen, Austria). Details of library synthesis are presented in Supplementary Information Method S5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FXN-F (TGGAATGTCAAAAAGCAGAGTG), FXN-R (CCACTCCCAAAGGAGACATC), β-2-Microglobulin-F (GCTCGCGCTACTCTCTCTTT), β-2-Microglobulin-R (CGGATGGATGAAACCCAGACA) 25 , and β-actin-F (GGGTCAGAAGGATTCCTATG), β-actin-R (GGTCTCAAACATGATCTGGG).…”
Section: Methodsmentioning
confidence: 99%